Caracterização tecnológica da madeira de Maclura tinctoria (L.) D. Don ex steud. - Freitas, Danilo Leão de (2016)
The objective of this study was to characterize technologically the wood of Tajuva (Maclura tinctoria). Therefore, there were physical, mechanical tests, of accelerated rot fungi in the laboratory and colorimetric analysis of the wood. Five trees of the species were collected from a natural forest stand located in the municipality of Porto Mauá, Rio Grande do Sul. After the selection of the same, these were cut into logs, and then split into planks for the preparation of specimens for performing the timber characterization tests. The evaluation of physical and mechanical properties was carried out according to D143-94 standard - ASTM (2005). The accelerated rotting test followed the standard D-2017 - ASTM (2005). The analysis of the staining of the heartwood and sapwood of the timber, and the colorimetric change of the logs after being subjected to fungal attack, were performed using the color measuring system CIELAB 1976. The results showed a decrease in specific gravity and green density towards base top of the tree, while the maximum moisture content showed an increase in the same direction. The weighted basic density presented by the species was 0.555 g.cm-3, and the bulk density of 12% equal to 0.70 g.cm-3. The timber had a good dimensional stability. The bulk density of the wood showed high and significant correlation with the bending, hardness tension in the proportional limit and maximum resistance to compression parallel and perpendicular compression. Thus, the specific gravity becomes important variable for predicting the strength of wood regarding mechanical properties. The mechanical properties allowed classifying the wood of this species as medium strength high. The heartwood and sapwood showed a distinct color: while the core was characterized by yellow, sapwood presented grayish-white color. The region of the heart showed high resistance to attack of fungi Pycnoporus sanguineus and Gloeophyllum trabeum with a weight loss equal to 1.52% and 0.96%, respectively. While the sapwood showed moderate resistance to attack of the fungus Pycnoporus sanguineus, with mass loss in value of 40.4%, and high resistance to fungal attack of Gloeophyllum trabeum, with 8.4% of weight loss. As for the indications of this wood uses, may be indicated for rural buildings, such as fence posts, pillars, posts, sleepers and bridge beams, and construction as rafters, beams and floors.